POLITICS AT THE MUSEUM: THE APPEARANCES OF MUSEUM SONOBUDOYO AND MONUMEN YOGYA KEMBALI, YOGYAKARTA - Sektiadi (Berkala Arkeologi, 2011)
Museum was a man-made thing, a culture. This situation made the museum polluted with many tension, especially for the museum founded or managed by the government. This paper tried to evaluate the appeareance of the State Museum of DIY "Sonobudoyo" as a general museum and Jogja Kembali Monument as a tematic museum, and found some political aspects involved in their buildings, collections, exhibitions and other things